Validation and Quantification of Domperidone in Spiked Plasma Matrix Using Reversed Phase HPLC-UV Method - Sekar Ayu Pawestri; Akhmad Kharis Nugroho; Endang Lukitaningsih; Purwantiningsih Purwantiningsih (Universitas Gadjah Mada, 2021)
Pharmacokinetics studies of domperidone generally analyze plasma matrix samples. The present work aimed to develop and validate a rapid and simple reversed phase-HPLC method for quantifying domperidone in plasma matrices. The chromatographic method implemented: 1. Luna Phenomenex® C18 (250 mm × 4.6 mm i.d; 5 µm) column, 2. isocratic mobile phase mixture of phosphate buffer 0.02 M:acetonitrile (70:30, v/v) with a flow rate of 1 mL/min, 3. UV detection at 285 nm. Domperidone and propranolol hydrochloride (as internal standard) were extracted from the deproteinated plasma sample. The method linearity was 0.998 in the range concentration of 15–200 ng/mL. The percentage of accuracy error was between -8.49–4.31%, while the percentage coefficient variation of precision ranged between 5.11–14.24%. This proposed method was simple, rapid (separation time less than 10 min), and selective. The validation parameters responses satisfied the method's requirements to determine domperidone in a plasma sample.